1999
DOI: 10.1002/hep.510290242
|View full text |Cite
|
Sign up to set email alerts
|

Acute carbon tetrachloride feeding selectively damages large, but not small, cholangiocytes from normal rat liver

Abstract: The aim of this study was to develop a model of selective duct damage restricted to hormone-responsive segments corresponding to the ducts damaged in primary biliary cirrhosis (PBC). Carbon tetrachloride (CCl 4 ) was fed by gavage to rats, and 2, 7, 14, and 28 days later, small and large cholangiocytes were isolated. Apoptosis was determined in situ by morphology and in purified cholangiocytes by assessment of nuclear fragmentation by 4,6-diamidino-2-phenylindole (DAPI) staining. Cholangiocyte proliferation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
188
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(199 citation statements)
references
References 55 publications
(236 reference statements)
10
188
1
Order By: Relevance
“…Similarly, in isolated bivascularly perfused rat liver, arterial infusion of ACh accentuates secretin-stimulated HCO 3 − secretion (118). A decrease of secretin-stimulated bile flow and HCO 3 − secretion, was observed in cholangiocytes isolated from the liver of bile duct-ligated rats with total vagotomy; this further supports the role of parasympathetic innervation and its neurotransmitter, ACh, in the potentiation of secretin-stimulated HCO 3 − secretion (165,178,180,181).…”
Section: Potentiation Of Secretin-stimulated Cholangiocyte Secretionsupporting
confidence: 57%
“…Similarly, in isolated bivascularly perfused rat liver, arterial infusion of ACh accentuates secretin-stimulated HCO 3 − secretion (118). A decrease of secretin-stimulated bile flow and HCO 3 − secretion, was observed in cholangiocytes isolated from the liver of bile duct-ligated rats with total vagotomy; this further supports the role of parasympathetic innervation and its neurotransmitter, ACh, in the potentiation of secretin-stimulated HCO 3 − secretion (165,178,180,181).…”
Section: Potentiation Of Secretin-stimulated Cholangiocyte Secretionsupporting
confidence: 57%
“…12 In the intrahepatic biliary tree, there are different proliferative compartments that differentially respond to the aforementioned liver injury/toxins. 3,6,8,9,11 Consistent with this novel concept, in rats with BDL only large cholangiocytes undergo replication with enhanced DNA replication and increased number of large bile ducts. 3 Furthermore, a single dose of CCl 4 (administered to rats by gastric gavage) induces ductopenia of large ducts whereas small ducts de novo proliferate to compensate for the loss of proliferative activity of large ducts.…”
mentioning
confidence: 73%
“…In animal models, cholangiocytes markedly proliferate in response to a number of pathological maneuvers including bile duct ligation (BDL), [2][3][4][5][6] partial hepatectomy, 7,8 or feeding of carbon tetrachloride (CCl 4 ), 6,9 ␣-naphthylisothiocyanate (ANIT), 10,11 or specific bile salts. 12 In the intrahepatic biliary tree, there are different proliferative compartments that differentially respond to the aforementioned liver injury/toxins.…”
mentioning
confidence: 99%
“…Two days after CCl 4 administration there was an increased number of small ducts but a reduction in large ducts. 18 Both large and small cholangiocytes during the regrowth of the intrahepatic biliary tree after 70% hepatectomy were involved in proliferative processes. 17 Examination of cholangiocyte growth assessed in situ by morphometry of the number of small and large cholangiocytes and by assessment of H 3 histone and proliferating cell nuclear antigen mRNA expression in small and large cholangiocytes revealed that both proliferate in response to ANIT feeding.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,10 Moreover, the rodent biliary tree undergoes selective proliferation in response to different experimental stimuli such as bile duct ligation, 6,8,[11][12][13][14] 70% hepatectomy, [15][16][17] CCl 4 treatment, 18 and feeding of ␣-naphthylisothiocyanate (ANIT), a chemical substance the chronic administration of which produces a dose-and time-dependent cholangiocyte proliferative response in rats. 19 -25 However, the anatomical basis for and the nature of the remodeling process of the biliary tract in response to these stimuli remain unclear.…”
mentioning
confidence: 99%